Research on Elastic Loads Participating in Demand Response Based on the Price Mechanism and the Demand Elasticity. Issue 1 (August 2021) - Ding, Yifan; Ma, Yahui; Jiang, Haiyan; Xi, Weimin
Abstract: Elastic load can be regarded as a demand response resource, such as the temperature-controlled loads, the energy storage and the electric vehicles. It participates in the operation and dispatch of the power grid, and its position is becoming more and more important in the future power system. Due to the complex economic environment of the power market, all users involved in demand response are required to interact with each other to obtain an efficient control and dispatch method. From the perspective of user economy, this article takes the minimum total cost of user electricity as the objective function to optimize the load demand response. Two different algorithms, the particle swarm algorithm and the nonlinear algorithm, are used to solve the problem. The results show that the application of particle swarm optimization in the elastic load demand response has obvious characteristics and advantages.